National Trends and Reported Risk Factors Among Pregnant Women With Syphilis in the United States, 2012–2016. Issue 1 (January 2019) - Trivedi, Shivika; Williams, Charnetta; Torrone, Elizabeth; Kidd, Sarah
Abstract : OBJECTIVE: To describe recent syphilis trends among pregnant women and to evaluate the prevalence of reported high-risk behaviors in this population. METHODS: We analyzed U.S. national case report data for 2012–2016 to assess trends among pregnant women with all stages of syphilis. Risk behavior data collected through case interviews during routine local health department investigation of syphilis cases were used to evaluate the number of pregnant women with syphilis reporting these behaviors. RESULTS: During 2012–2016, the number of syphilis cases among pregnant women increased 61%, from 1, 561 to 2, 508, and this increase was observed across all races and ethnicities, all women aged 15–45 years, and all U.S. regions. Of 15 queried risk factors, including high-risk sexual behaviors and drug use, 49% of pregnant women with syphilis did not report any in the past year. The most commonly reported risk behaviors were a history of a sexually transmitted disease (43%) and more than one sex partner in the past year (30%). CONCLUSION: Syphilis cases among pregnant women increased from 2012 to 2016, and in half, no traditional behavioral risk factors were reported. Efforts to reduce syphilis among pregnant women should involve increasing health care provider awareness of the Centers for Disease Control and Prevention and the American College of Obstetricians and Gynecologists' recommendations, which include screening all pregnant women for syphilis at the first prenatal visit and rescreening high-risk women during the third trimester and at delivery. Health care providers should also consider local syphilis prevalence in addition to individual reported risk factors when deciding whether to repeat screening. Abstract : Reported cases of syphilis among pregnant women have increased in every demographic group, and only approximately 50% of pregnant women with syphilis report high-risk behaviors.